2012
DOI: 10.1159/000329178
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychotherapy on Psychological Well-Being and Diurnal Cortisol Patterns in Breast Cancer Survivors

Abstract: Background: Neuroendocrine dysregulation influenced by psychosocial stress is related to breast cancer recurrence. Very few studies examine the impacts of psychotherapy on diurnal cortisol patterns among breast cancer survivors. Methods: Forty-eight breast cancer patients who completed active cancer treatment were randomly assigned to receive either 8 weekly body-mind-spirit (BMS) group therapy sessions or 1 educational (EDU) session. Self-report measures included the Beck Depression Inventory-II (BDI-II), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 60 publications
(50 reference statements)
2
44
0
3
Order By: Relevance
“…In addition, the types of cortisol parameters measured, along with their patterns of change, were not uniform across studies. Two studies, one evaluating mindfulness-based cancer recovery and supportive expressive therapy [25], and the other evaluating mind-body-spirit therapy [34], found that the diurnal slope remained unchanged in the treatments groups but that it became significantly flatter in the control group, suggesting that these treatments had a buffering effect on the HPA axis. This finding corresponded with clinical findings in only one of the studies [25], however.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the types of cortisol parameters measured, along with their patterns of change, were not uniform across studies. Two studies, one evaluating mindfulness-based cancer recovery and supportive expressive therapy [25], and the other evaluating mind-body-spirit therapy [34], found that the diurnal slope remained unchanged in the treatments groups but that it became significantly flatter in the control group, suggesting that these treatments had a buffering effect on the HPA axis. This finding corresponded with clinical findings in only one of the studies [25], however.…”
Section: Resultsmentioning
confidence: 99%
“…However, as fluctuations can be assumed to be at random, a systematic bias of the results is unlikely, rather the strength of the associations may have been underestimated. Cortisol patterns based on only single day collection have also shown meaningful associations with behavioral parameters as well as health outcomes in many other studies [43,[50][51][52][53]. Further, sampling times were self-reported and we had no control over whether the morning sample was really taken immediately after awakening.…”
Section: Discussionmentioning
confidence: 98%
“…El subtipo de psicoterapia breve más utilizada, derivada del proceso psicoanalítico, hace referencia a la terapia psicodinámicamente orientada [71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], y en uno de los artículos se plantea la posibilidad de diseñar un estudio que compare este tipo de intervenciones con otros modelos psicoterapéuticos [96]. Si bien no se menciona el número mínimo de sesiones necesario para garantizar una adecuada intervención, se recomienda que, como todo proceso psicoterapéutico, se centre en el individuo que se beneficiaría de ella, más que en intentar plantear una fórmula o algoritmo para reproducirlo de manera autónoma.…”
Section: Psicoterapia Breve (12 %)unclassified